Engineered materials and metamaterials : design and fabrication - Dudley, Richard A., 1979-; Fiddy, M. A. (SPIE tutorial texts ;, 2017)
"The field of metamaterials arose from a deeper understanding of how electromagnetic waves interact with materials and subwavelength-scaled scattering structures. This opened up the field of metamaterials or engineered materials through advances in understanding how material properties not found in nature could be designed along with advances in fabrication capabilities. Metamaterial advances span the electromagnetic spectrum, with examples being more common at lower (e.g., microwave) frequencies. The microwave or x-band regime has proven to be a good testbed for the first generation of metamaterials, but recently we have seen optical and IR metamaterials emerging as well. The exploitation of these more complex material-wave interactions, based on arrangements of subwavelength scale components, has generated a lot of global activity. We can, in principle, engineer material properties to greatly extend those currently available. This tutorial text presents both the usual and unusual electromagnetic properties of materials, focusing especially man-made or engineered metamaterials. After a review of Maxwell's equations and material properties, the idea of resonant meta-atoms and composite media are introduced. The fabrication of metamaterials and the properties of negative index materials are explained. The difficulties associated with reducing the size of meta-atoms for use at optical frequencies are described, and the use of metamaterials for superresolution imaging is presented in some detail"--